Photodegradation of Cationic Dyes in Aqueous Solutions by BIOI/SRHA Nanoparticles - Mohammed K. Kzar; Zaki N. Kadhim; Ali H.Al-Mowali (Genius Journals, 2022)
In this research, we discuss the removal of basic fusion (BF), and crystal violet(CV) dyes by strontium hydroxyapatite supported BiOI. A modified hydrolysis model, one can synthesise BiOI/SrHA. BiOI/SrHA was characterized using Fourier transform-infrared spectroscopy (FTIR), UV-visible (UV-vis) analysis, X-ray diffraction (XRD), energy diffraction X-ray (EDX), and scanning electron microscopy (SEM). SEM outcome confirmed the dispersion of BiOI onto strontium hydroxyapatite. The shape of the BiOI catalytic samples overlapped with each other to form 3D hierarchical flower-like structures. The UV-visible was used as a radiation source during photocatalysis. BiOI/SrHA had an effect on malachite green dye degradation. The oxidative removal occurred through hydroxyl radical formation. UV-visible (UV-vis) BiOI/SrHA showed perfect photocatalytic property for the decay of Basic Fuchsin (BF) and Crystal Violet (CV) from an aqueous solution. According to kinetics analysis, the dye degradation rates could be in a pseudo-first-order model.
Keywords: bismuth oxyiodide; strontium hydroxyapatite; cationic dyes; photocatalytic